Characteristics of food consumption during the COVID-19 pandemic among residents of the metropolitan region of Belém - Raiol, Thayane Cristina Souza; Silva, Eullén de Paula Dos Santos da; Miranda, Luana Cristina Costa de; Nascimento, Mayko Guimarães (Seven Editora, 2023)
INTRODUCTION: Food is important for a healthy life, should be varied and of nutritional quality. Given this, a research was developed addressing dietary variables of the residents of the metropolitan region of Belém, Marabá and Santarém during the first peak of the pandemic of the new coronavirus. OBJECTIVES: To observe the dietary practices of participants from March to August 2020. METHODOLOGY: The present study was a research project developed by the Academic League of Collective Health and Parasitology, of the UNINASSAU University Center, where the electronic form (Google forms) was used in which the participants (over 18 years old) answered objective questions related to the period of the pandemic, mainly about the food consumed. This study was approved by the CEP of the Evandro Chagas Institute on 08/21/2020 with the opinion of n° 4.229.578. RESULTS AND DISCUSSION: With social isolation, 89.8% of the 275 respondents claimed a decrease in trips to supermarkets. Regarding the change in food consumption, it was observed: 33.1% stated that they had not changed their eating habits, 18.5% were consuming a greater amount of industrialized foods, 23.3% were consuming industrialized and natural foods, and 25.1% were consuming a greater amount of natural foods, which is positive, because these foods contribute to the strengthening of the immune system. In addition, the frequency of consumption of certain foods was addressed, in which there was a higher percentage for fruits and vegetables with 62.5% and 59.6%, respectively. However, a significant value for pasta (46.9%) and sweets (38.5%). CONCLUSION: The changes reported by the participants show a qualitative improvement in the diet from the increase in the consumption of fruits and vegetables, but there are marked percentages of the consumption of pasta and sweets. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-006